Respostas do matrinxã ( Brycon cephalus) a anestésicos e estressores - Inoue, Luís Antônio Kioshi Aoki (2005)
Commercial fish farming has been viable for industry in Brazil. National production is around 120 thousand tons/year. In this way, large amount of fishes are handled every day in our farms. However, drastic consequences are sometimes observed due to the high sensitivity of some tropical fish to handling procedures. Matrinxã (Brycon cephalus) is a native species that is very sensitive to handling, in which mortality is usually observed. So stress studies in tropical fish in aquaculture facilities are important as farmers need more information about these fish stress and alternatives for fish management. The present work evaluated some matrinxã stress responses, and the use of anesthetics as eugenol, benzocaine and 2-phenoxyethanol to reduce the stress during field procedures. Matrinxã is responsive to fish farm stressors as handling, transport and thermal shocks. Increases of plasma cortisol, glucose, lactate and ammonia indicated acute primary and secondary stress responses of matrinxã. Plasma ions (Na, Cl and K) and protein unbalance were observed. Liver glycogen indicated the high energetic cost to matrinxã cope with the studied stressors. Stress responses at the cellular level were not detected in matrinxã as hsp-70 expressions were not altered. Other proteins expressions may be related to matrinxã celular stress, which requires new studies in the future.